ON SEEING MOUSE AND THINKING HUMAN: EXPERIMENTAL SCIENCE, CORPOREAL EQUIVALENCE, AND THE LITERARY MODEL ORGANISM - Sheridan, Jordan (My University, 2019)
This thesis examines literary texts that represent encounters with model organisms in ways that enact an interspecies ethics that turns the narrative of bodily relationality embedded within the model organism into a source of care, friendship, respect, and mourning. My project understands model organisms as material beings as well as semiotic and narrative entities; I suggest that the very ‘materiality’ of the model organism’s body is symbolic precisely because it is designed to refer to bodies other than its own. The model organism involves a double relationality between the categories of ‘animal’ and ‘human’ because it serves as a mediator between human nature and nature at large. This is not to say that that human biology is not part of ‘nature’ but rather that anthropocentric and human exceptionalist ideologies pervade discourses of human biology and thus the model organism provides a link to our biological and corporeal ‘selves’ in a way that maintains species divisions. The texts I analyze throughout this dissertation offer alternative ways of thinking about the model organism by exposing the multiple meanings and narratives that coexist within them both as representations and as living sentient beings. This project centers around two questions: How do cultural texts represent and negotiate disconnects between how model organisms signify within scientific discourses and their broader cultural identities? How does literature specifically engage with scientific knowledge in ways that both disrupt and affirm the status of the model organism as a scientific object?
Keywords: Animal Studies, Science and Technology Studies, Literary Theory, Narratology, Poetics, Model Organism, Biopolitics, Genomics, Postgenomics, Post Humanism, Mice, Laboratory Animal, Embodiment